2021
DOI: 10.1002/viw.20200110
|View full text |Cite
|
Sign up to set email alerts
|

Quickly evolving near‐infrared photoimmunotherapy provides multifaceted approach to modern cancer treatment

Abstract: Among modalities of cancer immunotherapy, near-infrared photoimmunotherapy (NIR-PIT) has reached significant preclinical and clinical stages and quickly evolved over the last 5 years. NIR-PIT uses deep-penetrable NIR light to induce physicochemical changes in the antibody-photosensitizer conjugate (APC), leading to resultant necrosis and immunogenic cell death (ICD) of the cancer cells. Alternatively, other types of photomedicine use photosensitizers to convert absorbed light energy either into reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 160 publications
(257 reference statements)
0
30
0
Order By: Relevance
“…46 Most studies focus on evaluating the migration and function of cytotoxic T lymphocytes in a model of adoptive transfer immunotherapy or Chimeric antigen receptor (CAR) T cell therapy, and the effector cells are detected by flow cytometry and microscopy days after labeling. 47 The exogenous labeling is generally performed by incubating cells with lipophilic fluorophores. 48 There are two primary mechanisms of entry into the cell: (1) direct fusion with the plasma membrane and (2) endocytosis.…”
Section: "Ex Vivo" Labeling For Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Most studies focus on evaluating the migration and function of cytotoxic T lymphocytes in a model of adoptive transfer immunotherapy or Chimeric antigen receptor (CAR) T cell therapy, and the effector cells are detected by flow cytometry and microscopy days after labeling. 47 The exogenous labeling is generally performed by incubating cells with lipophilic fluorophores. 48 There are two primary mechanisms of entry into the cell: (1) direct fusion with the plasma membrane and (2) endocytosis.…”
Section: "Ex Vivo" Labeling For Immune Cellsmentioning
confidence: 99%
“… 46 Most studies focus on evaluating the migration and function of cytotoxic T lymphocytes in a model of adoptive transfer immunotherapy or Chimeric antigen receptor (CAR) T cell therapy, and the effector cells are detected by flow cytometry and microscopy days after labeling. 47 …”
Section: Nir Fluorescence Imaging Of Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first few years that followed, researchers explored the degree of substitution on the mAB and different linking methods [ 279 , 280 ]. Currently, several reviews concerning this topic were published in the last two years and clinical trials are ongoing [ 281 , 282 , 283 , 284 , 285 ]. Given that these recent reviews cover the topic in detail, antibody–PS conjugates will not be covered in more detail in this particular review.…”
Section: How To Tame the Bulletmentioning
confidence: 99%
“…Each group received a single dose infusion of AuroShell (TM) particles followed by interstitial illuminations with an 808 nm laser, followed by monitoring for 6 months. It was found that the treatment was followed by few adverse side effects [ 192 ].…”
Section: Introductionmentioning
confidence: 99%